Abundance of Macrozoobenthos in the Seagrass Field Ecosystem in Cemara Besar Island, Karimunjawa Islands - Ria Azizah; Bagus Darmawan; Nur Taufiq SPJ (Jurnal Moluska Indonesia, 2020)
Seagrass has several important ecological functions which protected some species of invertebrates such as crustaceans, bivalves, gastropods, echinoderms, and other marine organism. Seagrass have ecological processes, where any interaction of several biotic and environment components. One of the biotic components associated with seagrass is macrozoobenthos. This study aims to determine the type and abundance of macrozoobenthos, the value of ecological index and covering percentage of seagrass at Cemara Besar Island, Karimunjawa. This study was conducted at Cemara Besar Island, Karimunjawa. The method used in this study was survey method with descriptive data analysis. Measurement of seagrass and macrozoobenthos using transect quadrant size of 1 x 1 meter. Macrozoobenthos living on the surface susbtrat (epifauna) was taken directly, while macrozoobenthos living within the substrate (infauna) using a corer was inserted into the substrate to a depth of 25cm. After conducting the samples were treated, the sediment sample sieved using benthos filter with a pore diameter of 1 mm and put macrozoobenthos into a sample bottle which has been given a 4% formalin solution and dye rose bengal, then identification of macrozoobenthos using a microscope and magnifying glass. Macrozoobenthos samples were analyzed using the calculation of abundance, the diversity index, the evenness index and the domination index. The result show that, in seagrass ecosystems in Cemara Besar Island Karimunjawa was found 4 classes macrozoobenthos consisting of Bivalve 3 species, Polychaeta 5 speseies, Echinoidea 4 species, and Gastropoda 25 species. The value of abundance in marine protection zone ranging from 6.32 to 8.42 ind/dm3 and the value of abundance in utilization zone marine ranging from 6.85 to 7.37 ind/dm3. The value of diversity index in the marine protection zone ranging from 1.42 to 2.57 are included in the category of low to moderate, while in the Marine Utility Zone ranging from 3.26 to 3.47 are included in the high category. The value of evenness index in the marine protection zone (E = 0.61 to 0.74) and utility zone (E = 0.77 to 0.82) were included in the high category (E > 0.6) in the second zone. The value of domination index in the marine protection zone (C = 0.20 - 0.48) and utility zone (C = 0.13 - 0.17) indicates that there are not macrozoobenthos species dominates. The Percentage cover of seagrass in marine protection zone from 68.75 to 76.04%, while the percentage cover of seagrass in utility zone ranging from 59.38 to 65.63%.